Thyrotropin-luteinizing hormone/chorionic gonadotropin receptor extracellular domain chimeras as probes for thyrotropin receptor function. - Nagayama, Y (1991)
To define the sites in the extracellular domain of the human thyrotropin (TSH) receptor that are involved in TSH binding and signal transduction we constructed chimeric thyrotropin-luteinizing hormone/chorionic gonadotropin (TSH-LH/CG) receptors. The extracellular domain of the human TSH receptor was divided into five regions that were replaced, either singly or in various combinations, with homologous regions of the rat LH/CG receptor. The chimeric receptors were stably expressed in Chinese hamster ovary cells. The data obtained suggest that the carboxyl region of the extracellular domain (amino acid residues 261-418) and particularly the middle region (residues 171-260) play a role in signal transduction. The possibility is also raised of an interaction between the amino and carboxyl regions of the extracellular domain in the process of signal transduction. With respect to hormone binding, substitution of the entire extracellular domain of the LH/CG receptor for the corresponding region of the TSH receptor resulted in high-affinity human CG binding with complete loss of TSH binding. Surprisingly, however, there was at least one chimera with a substitution at each of the five domains that still retained high-affinity TSH binding. Substitution of residues 1-170 of the TSH receptor with the corresponding region of the LH/CG receptor was associated with the retention of high-affinity TSH binding but ligand specificity was lost in that TSH and human CG could interact functionally with the receptor. In summary, these studies suggest that the middle region and carboxyl half of the extracellular domain of the TSH receptor are involved in signal transduction and that the TSH-binding region is likely to span the entire extracellular domain, with multiple discontinuous contact sites.